Adsorptive removal of methylene blue using magnetic biochar derived from agricultural waste biomass: Equilibrium, isotherm, kinetic study - Ruthiraan, M.; Abdullah, E.; Mujawar, Mubarak; Nizamuddin, S. (2018)
© 2018 World Scientific Publishing Company. Wastewater discharge from textile industries contribute much to water pollution and threaten the aqua ecosystem balance. Synthesis of agriculture waste based adsorbent is a smart move toward overcoming the critical environmental issues as well as a good waste management process implied. This research work describes the adsorption of methylene blue dye from aqueous solution on nickel oxide attached magnetic biochar derived from mangosteen peel. A series of characterization methods was employed such as FTIR, FESEM analysis and BET surface area analyzer to understand the adsorbent behavior produced at a heating temperature of 800âC for 20min duration. The adsorbate pH value was varied to investigate the adsorption kinetic trend and the isotherm models were developed by determining the equilibrium adsorption capacity at varied adsorbate initial concentration. Equilibrium adsorption isotherm models were measured for single component system and the calculated data were analyzed by using Langmuir, Freundlich, Tempkin and Dubinin-Radushkevich isotherm equations. The Langmuir, Freundlich and Tempkin isotherm model exhibit a promising R2-correlation value of more than 0.95 for all three isotherm models. The Langmuir isotherm model reflectsan equilibrium adsorption capacity of 22.883mg.g-1.